2010
DOI: 10.3133/sir20105073
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of magnitude and frequency of floods in urban basins in Missouri

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit http://store.usgs.gov Any use of trade, product, or firm names is for descriptive purposes only and does not imply endorsement by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…As previously mentioned, IMPERV was not a statistically significant explanatory variable at the 95-percent confidence level for any of the exceedance probabilities examined. Despite this lack of significance in this analysis, other studies (Robbins and Pope, 1996;Southard, 2010;Gotvald and Knaak, 2011) found that imperviousness is an important predictor of the magnitude of flood flows. The exploratory statistical analysis done in this study indicated that IMPERV provided some explanatory power, generally ranking fifth or sixth among the variables examined.…”
Section: Urban Influencementioning
confidence: 57%
See 1 more Smart Citation
“…As previously mentioned, IMPERV was not a statistically significant explanatory variable at the 95-percent confidence level for any of the exceedance probabilities examined. Despite this lack of significance in this analysis, other studies (Robbins and Pope, 1996;Southard, 2010;Gotvald and Knaak, 2011) found that imperviousness is an important predictor of the magnitude of flood flows. The exploratory statistical analysis done in this study indicated that IMPERV provided some explanatory power, generally ranking fifth or sixth among the variables examined.…”
Section: Urban Influencementioning
confidence: 57%
“…The reason for this is that, during large storms, soils become saturated, preventing further infiltration; this causes surface runoff to increase similar to the effect an impervious surface has for any size storm. Nevertheless, urban adjustments to regionalized flood flow equations for rural basins have been made to include some measure of urbanization, such as impervious surface (Southard, 2010), population density (Watson and Schopp, 2009), or composite urban indices, such as the basin development factor, which accounts for impervious surface as well as storm sewers, culverts, and stream channel alterations (Sauer and others, 1983;Sherwood, 1994).…”
Section: Urban Influencementioning
confidence: 99%
“…Study of other regions with these methods is warranted. Until this is done and the realism of the predictions improved, empirical methodologies for peak discharge estimation (e.g., Soong, Ishii, Sharpe, & Avery, ; Southard, ) will be superior for planning purposes. Nevertheless, only the comparison of theoretical predictions to observations can provide fundamental insight into the nature of hydrologic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Huizinga (2007) updated the two-dimensional model of a 2-mile reach developed by Kelly and Rydlund (2006) in a subsequent study to simulate the potential effects of channel modifications and a proposed grade control structure in the Blue River. Southard (2010) developed regression equations to determine the magnitude and frequency of floods in urban areas in Missouri that included Blue River, Indian Creek, and Brush Creek by using streamgage records in the development of these equations. These regression equations, for which drainage area and percent impervious area are explanatory variables, were used to compute flood streamflows for the 50-, 20-, 10-, 1-, and 0.2-percent AEP flows at the study streamgages (table 2).…”
Section: Previous Studiesmentioning
confidence: 99%